Business communication in Poland: sale promotion, advertising, public relations and virtual communication - Lewicka, Hanna (Komunikacja biznesowa w Polsce: promocja sprzedaży, reklamowanie, publiczne relacje i wirtualna komunikacja, 2015)
Business communication is a key activity for every business, as every business has to deal with its external and internal environment. It describes many business activities and can be taken under consideration from different perspectives, but still the basic communication activities can consider any company in the world. However, the cultural aspect determines the realization of every activity. In different countries the way a business communicates with customers, or business actors do it within the company, differs respectively to national traditions, values and beliefs. The aim of the following article is to present, analyse and explain the way of business communication in Poland. As every country, it has a specific characteristics that is distinctive only for its own, which deeply affects various aspects of business communication
Społeczeństwo i Ekonomia = Society and Economics, 2015, Nr 2 (4), s. 68-84
Keywords: Poland; communication; business; channels; advertising; public relations; customers; social media; komunikacja; biznes; kanały komunikacji; reklama; konsumenci; media społecznościowe